Determinants of Unmet Need for Hormonal Contraception in Couples of Fertilizing Age (PUS) at the Faculty of Public Health, University of Muslim Indonesia - Nia Karuniawati; Fatma Jama; Andi Masnilawati (Pancasakti Journal Of Public Health Science And Research, 2025)
The high rate of unmet need is a demographic phenomenon that constitutes an important aspect to consider in the future development of family planning programs. Unmet need refers to married women who are sexually active but do not use contraceptive methods, despite expressing a desire either to delay childbearing or to stop having children altogether. One of the consequences of unmet need is the increased incidence of unintended pregnancies (UPs). Unintended pregnancies include both mistimed and unwanted pregnancies. This study aimed to analyze the determinants of unmet need for hormonal contraception among female students at the Faculty of Public Health, Muslim University of Indonesia. This research employed an analytical survey method with a cross-sectional study design. The sampling technique used was total sampling, and data were collected using a structured questionnaire. Statistical analysis was performed using the Chi-square test. The findings revealed no significant association between parity and unmet need for hormonal contraception (P-value = 0.541 > α = 0.05), no significant association between contraceptive side effects and unmet need (P-value = 0.061 > α = 0.05), and no significant association between husband support and unmet need (P-value = 1.000 > α = 0.05). There is no significant relationship between parity, side effects, or husband support and the unmet need for hormonal contraception.